Current Scope of Online Ophthalmology Education and Curriculum Impact Due to COVID-19 - Patrick S. Y. Lee (Thieme Medical Publishers, Inc., 2021)
Objective Abrupt changes in ophthalmology education caused by the COVID-19 pandemic have resulted in novel online curriculum development. The aims of this study were to identify (1) the scope of online curricula implemented both prior to and during the COVID-19 pandemic; (2) perception of educators on these online modalities; and (3) early lessons from online implementation that may guide future curricular planning. Methods Implementation of online curricula was evaluated by using a national online survey of Ophthalmology Directors of Medical Student Education (DMSE) via Qualtrics software. Participants Medical Student Educators of the Association of University Professors of Ophthalmology (AUPO) were surveyed. Results Fifty responses were collected, representing a 64.9% response rate. Prior to the COVID-19 pandemic, 44% of institutions had no online components in their courses, but 78.3% of institutions reported increasing online components in response to the pandemic. Required courses were significantly associated both with having implemented online components before the pandemic and implementing online-only versions of these courses in response to the pandemic. The three most popular modalities used for online teaching were lectures, interactive cases, and problem-based learning, with a median satisfaction of 4.0, 4.32, and 4.35, (out of five) respectively. The least popular modalities used were online teaching of physical exam skills and telemedicine, both with a median satisfaction of 2.5. Median overall educator satisfaction with online teaching was four (out of five). The most common weakness related to online teaching was the lack of effective physical exam skills training. Conclusion Our data demonstrate that most institutions successfully shifted their ophthalmology curriculum to a virtual and online version in response to the COVID-19 pandemic. DMSEs adapted quickly, transitioning in-person clinical courses, and extracurricular activities to online formats. Overall, educator satisfaction with online curricula was high. Integration of online curricula provides the opportunity to enrich institutional curriculums and overcome limitations imposed by decreasing curriculum time. This study reveals an early window into the utilization, strengths, and weaknesses of online ophthalmology education, which can serve as a guiding point to enhance ophthalmology curriculum development.